A KDP crystal atomic-level surface polishing liquid, a preparation method and application thereof

CN122465501BActive Publication Date: 2026-10-20HANGZHOU DIANZI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610931993.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-10-20
Estimated Expiration
2046-06-26

AI Technical Summary

Technical Problem

[0006]磨料粒径、硬度与分散性和KDP晶体软脆特性不匹配,抛光过程易产生划痕、崩边、解理坑及表面损伤,无法在限定微观区域内稳定实现原子级超光滑表面;

Benefits of technology

[0030]本发明应用于KDP晶体表面抛光,实现了在限定微观区域内稳定制备原子级超光滑无损伤表面(表面粗糙度最低可达Sa=0.284 nm),同时兼顾加工效率(最高可达1019.4nm/min)、低损伤、环保(采用天然添加剂)、高洁净度与光学使用性能,为KDP晶体高精度、绿色化抛光提供了有效解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122465501B_ABST
    Figure CN122465501B_ABST
Patent Text Reader

Abstract

The application discloses a KDP crystal atomic-level surface polishing liquid, a preparation method and application thereof, and belongs to the technical field of KDP crystal polishing.The polishing liquid comprises the following components: nanoscale silicon dioxide, grape seed extract, deionized water, and a mixed solution of anhydrous ethanol and 2,3-butanediol.The application is applied to KDP crystal surface polishing, realizes stable preparation of an atomic-level super-smooth non-damage surface in a limited micro area, and simultaneously considers processing efficiency, low damage, high cleanliness and optical use performance, and provides an effective solution for KDP crystal high-precision and green polishing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical mechanical polishing (CMP) technology, specifically to a method for preparing an atomic-level surface polishing slurry for KDP crystals and its application. It is suitable for high-precision surface polishing of KDP (potassium dihydrogen phosphate) crystals. Using a specific ratio of mixed solvent, nano-sized silica abrasive, and natural additives, combined with an appropriate polishing speed, high-precision polishing of specific microscopic regions of KDP crystals can be achieved, balancing polishing efficiency and surface quality. This improves the stability and controllability of the polishing process, reduces production costs, and meets the application requirements of KDP crystals in high-end fields such as laser inertial confinement fusion and precision optics. Background Technology

[0002] Potassium dihydrogen phosphate (KDP) crystals are indispensable nonlinear optical crystals in high-power laser systems, inertial confinement fusion devices, precision spectrometers, and quantum communication. They possess excellent electro-optic properties, nonlinear optical effects, and laser transmittance, making them a core functional material for high-end optical equipment. As laser systems evolve towards higher energy, higher beam quality, and higher stability, atomically precise requirements are placed on the surface quality of KDP crystals. Especially in critical optical working surfaces, atomically smooth surfaces must be stably achieved within designated microscopic observation areas, while ensuring the surface is free of scratches, chipping, deliquescence, corrosion, subsurface damage, and chemical residues to meet extremely high laser damage thresholds and long-term reliability requirements.

[0003] KDP crystals are characterized by low hardness, brittleness, easy cleavage, hygroscopicity, poor chemical stability, and significant anisotropy, making them one of the most difficult optical materials to achieve ultra-precision machining, internationally recognized. During processing, even minute mechanical stresses, chemical corrosion, or changes in environmental humidity can lead to cleavage cracks, pits, haze, and residual contamination on the surface, directly damaging the crystal's optical properties. Therefore, extremely stringent limitations are imposed on polishing slurry formulations, processing techniques, and surface control precision.

[0004] Currently, ultra-precision machining of KDP crystals mainly employs techniques such as single-point diamond turning (SPDT), magnetorheological polishing (MRF), ion beam polishing, and conventional chemical mechanical polishing (CMP). Among these, single-point diamond turning easily forms periodic cutting marks, wavy undulations, and subsurface damage layers on the crystal surface, making it difficult to obtain an atomically smooth surface. While magnetorheological polishing can improve surface accuracy, magnetic abrasive particles are easily embedded in the crystal surface, causing contamination, which is difficult and costly to clean, and it is difficult to consistently achieve atomic-level roughness within a limited microscopic area. Ion beam polishing offers high precision but has extremely low efficiency and expensive equipment, failing to meet the needs of mass industrial production.

[0005] Chemical mechanical polishing (CMP), with its synergistic mechanism of "chemical etching assistance + mechanical micro-removal," is currently the only ultra-precision machining method for KDP crystals that can balance efficiency, surface shape, and surface roughness. However, existing traditional CMP polishing slurries and processes suffer from several insurmountable technical drawbacks in KDP crystal processing:

[0006] The abrasive particle size, hardness and dispersion are not matched with the soft and brittle characteristics of KDP crystals, and the polishing process is prone to scratches, edge chipping, cleavage pits and surface damage, making it impossible to stably achieve an atomically ultra-smooth surface in a limited micro-region.

[0007] The solvent system has poor chemical compatibility with KDP crystals, which can easily cause crystal deliquescence, localized corrosion, surface whitening or haze, and damage the integrity of the crystal surface and optical transmittance.

[0008] Polishing additives are mostly toxic and harmful chemical reagents, which are not only environmentally unfriendly and harmful to the health of operators, but also easily form residual adsorption on the crystal surface, reducing the laser damage threshold of the crystal.

[0009] Existing polishing slurries have poor versatility and lack specificity. They have not been formulated to address the easy cleavage and deliquescence characteristics of KDP crystals, and therefore cannot simultaneously meet the requirements of processing efficiency, low damage, high cleanliness, and atomic-level high precision in the limited microscopic region. Summary of the Invention

[0010] To address the shortcomings of existing chemical mechanical polishing slurries for KDP crystals, this invention provides a method for preparing an atomic-level surface polishing slurry for KDP crystals and its application. This polishing slurry can achieve high-precision polishing of specific microscopic regions of KDP crystals, improve polishing efficiency and surface quality, enhance the stability and environmental friendliness of the polishing slurry, reduce environmental impact, and expand its application range.

[0011] To achieve the above objectives, the first aspect of this invention provides an atomic-level surface polishing slurry for KDP crystals. The slurry comprises the following components in the indicated mass percentages: 2-4% nano-sized silica, 1-3% deionized water, 0.5-1.5% grape seed extract, and the balance being a mixed alcohol. The mixed alcohol is composed of anhydrous ethanol and 2,3-butanediol. In the mixed alcohol, the mass percentage of anhydrous ethanol is 68.625%-72.75%, and the mass percentage of 2,3-butanediol is 22.875%-24.25%. The silica, used as the abrasive in the polishing slurry, is selected from nano-sized silica suitable for the soft and brittle characteristics of KDP crystals. The grape seed extract is a natural additive provided by Shandong Jinsheng Biotechnology Co., Ltd.

[0012] A portion of the grape seed extract molecules dissolve in a mixed solvent composed of water and mixed alcohols, while another portion is adsorbed at the molecular level onto the surface of the nano-sized silica, forming a steric hindrance effect that hinders the aggregation of the nano-sized silica. The nano-sized silica is uniformly dispersed in the mixed solvent.

[0013] Preferably, the particle size of the nano-sized silica is 20~50 nm.

[0014] Preferably, the nano-sized silica, anhydrous ethanol, 2,3-butanediol, grape seed extract, and deionized water are first mixed evenly by mechanical stirring, and then evenly mixed by ultrasonic dispersion and magnetic dispersion.

[0015] A second aspect of this invention provides a method for preparing the KDP crystal atomic-level surface polishing slurry, comprising the following steps:

[0016] (1) Weigh the raw materials according to the mass ratio described above: nano-sized silica, deionized water, grape seed extract, anhydrous ethanol and 2,3-butanediol;

[0017] Anhydrous ethanol and 2,3-butanediol were mixed evenly by mechanical stirring to prepare a mother liquor 0;

[0018] (2) Add nano-sized silica to mother liquor 0 and mix evenly by mechanical stirring to prepare polishing liquid 1;

[0019] (3) Add deionized water to the above polishing liquid 1 and mix evenly by mechanical stirring to prepare polishing liquid 2;

[0020] (4) Add grape seed extract to the above polishing liquid 2 and mix evenly by mechanical stirring to prepare polishing liquid 3;

[0021] (5) The polishing liquid 3 is ultrasonically dispersed, and finally the polishing liquid is magnetically stirred by a magnetic rotor to obtain KDP crystal atomic-level surface polishing liquid.

[0022] Preferably, in steps (1), (2), (3) and (4), the mechanical stirring speed is 1000-1200 rpm and the stirring time is 10-30 min.

[0023] Preferably, in step (5), the ultrasonic dispersion process involves an ultrasonic time of 15–30 min and an ultrasonic temperature of 25–30 °C.

[0024] Preferably, in step (5), the magnetic stirring speed is 600~800 rpm and the stirring time is 15~30 min.

[0025] The present invention also provides the application of the KDP crystal atomic-level surface polishing slurry, wherein the KDP crystal is polished according to the following parameters: polishing pressure 20~30 kPa, polishing disc rotation speed 70~80 rpm, polishing slurry flow rate 2 ml / min, polishing for 15 min.

[0026] Preferably, the KDP crystal is a square with a side length of 10 mm and a thickness of 5 mm.

[0027] Preferably, under the condition that the measurement range does not exceed 50×50 μm², after polishing, the KDP crystal has a surface arithmetic mean height Sa value of less than 0.301 nm, a peak-to-valley value PV value of less than 2.716 nm, and a root mean square roughness rms value of less than 0.373 nm.

[0028] Preferably, the material removal rate (MRR) is 784.1~941 nm / min.

[0029] Beneficial effects

[0030] This invention is applied to the surface polishing of KDP crystals, achieving stable preparation of atomically smooth, damage-free surfaces (with surface roughness as low as Sa=0.284 nm) within a limited microscopic area. It also takes into account processing efficiency (up to 1019.4 nm / min), low damage, environmental friendliness (using natural additives), high cleanliness, and optical performance, providing an effective solution for high-precision and green polishing of KDP crystals.

[0031] This invention overcomes the technical bottleneck of simultaneously achieving "hydrolysis inhibition, dispersion stability, and low-damage removal" in KDP crystal polishing by combining an anhydrous polar solvent system, nano-abrasive particle size control, and natural plant extract dispersant, resulting in a significant synergistic effect.

[0032] By combining solvent system and surface chemistry, the problem of "whether it can be polished" is solved: This invention uses a non-aqueous solvent system composed of anhydrous ethanol and 2,3-butanediol in a specific ratio to completely inhibit the hydrolysis reaction of KDP crystals from a chemical environment perspective, eliminating surface whitening and microcrack defects caused by hydrolysis; at the same time, this specific polar organic environment combined with grape seed extract provides a medium basis for the uniform dispersion of nano-SiO2 abrasives, avoiding secondary scratches caused by abrasive agglomeration.

[0033] By limiting the SiO2 abrasive particle size to between 20 and 50 nm and combining it with a solid content of 2 to 4 wt%, sufficient micro-cutting capability is ensured to achieve a high removal rate (up to 1019.4 nm / min), while avoiding the impact damage of large-particle abrasive to the soft and brittle KDP lattice, thus achieving a dynamic balance between "high efficiency" and "low damage." The SiO2 abrasive and solvent system work synergistically, utilizing glycol and a small amount of water to exert extremely weak swelling or complexation effects on the KDP surface lattice, weakening the surface molecular bond energy. Under mechanical shear force, the KDP surface bonds weakened by the chemical solvent are more easily broken, achieving atomic-level removal "primarily physical, supplemented by chemical," avoiding subsurface damage caused by pure mechanical polishing.

[0034] Grape seed extract (proanthocyanidins) was introduced as a functional dispersant. Its abundant phenolic hydroxyl groups form hydrogen bonds with the SiO2 surface in the organic system, constructing a strong steric barrier and overcoming the industry challenge of SiO2 nanoparticles easily settling and agglomerating in non-aqueous media. Simultaneously, when KDP crystals contain trace amounts of metal impurities, localized redox reactions (similar to micro-battery corrosion) may occur during polishing. Proanthocyanidins can chelate metal ions and quench free radicals, chemically preventing micro-pitting and discoloration on the crystal surface.

[0035] Through the above synergy, this invention achieves both atomic-level surface roughness (Sa ≤ 0.301 nm) and ultra-high removal rate (MRR ≤ 1019.4 nm / min) while ensuring that the KDP crystal is free from hydrolysis and corrosion. This is significantly better than existing technologies that improve the solvent or abrasive alone, and meets the ultimate optical quality requirements of inertial confinement fusion (ICF) devices for KDP crystal substrates. Attached Figure Description

[0036] Figure 1 The results show the surface roughness of KDP crystals after chemical mechanical polishing using the polishing slurry prepared in Example 1. a is a 3D surface profile of the KDP crystal, and b is an optical morphology image of the KDP sample. The surface Sa value of the polished KDP crystal was 0.301 nm, the measurement range was 50 × 50 μm², the PV value was 2.401 nm, and the rms value was 0.373 nm. The material removal rate (MRR) was 941 nm / min.

[0037] Figure 2The results show the surface roughness of KDP crystals after chemical mechanical polishing using the polishing slurry prepared in Example 2. In the figure, a is the 3D surface profile of the KDP crystal, and b is the optical morphology of the KDP sample. The surface Sa value of the polished KDP crystal is 0.293 nm, the measurement range is 50×50 μm², the PV value is 2.716 nm, the rms value is 0.368 nm, and the material removal rate MRR is 784.1 nm / min.

[0038] Figure 3 The table shows the surface roughness measurement results of KDP crystals after chemical mechanical polishing using the polishing slurry prepared in Example 3. Figure a shows the 3D surface profile of the KDP crystal, and figure b shows the optical morphology of the KDP sample. The surface roughness (Sa) of the polished KDP crystal was 0.284 nm, with a measurement range of 50 × 50 μm². The PV value was 2.456 nm, and the rms value was 0.354 nm. The material removal rate (MRR) was 1019.4 nm / min. Figure c shows the two-dimensional planar height diagram of the polished KDP crystal under atomic force microscopy (AFM), and figure d shows the three-dimensional profile diagram of the polished KDP crystal under AFM. The surface roughness (Sa) of the polished KDP crystal under AFM was 0.301 nm, with a measurement range of 5.2 × 5.1 μm². Detailed Implementation

[0039] The present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. The following embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0040] The first aspect of the present invention provides a KDP crystal atomic-level surface polishing liquid, the components of which include a mixed solvent (anhydrous ethanol: 2,3-butanediol), silica, deionized water, and grape seed extract.

[0041] The mixed solution is prepared by compounding anhydrous ethanol and 2,3-butanediol in a certain mass ratio, wherein the mass percentage of anhydrous ethanol is 68.625%~72.75% and the mass percentage of 2,3-butanediol is 22.875%~24.25%. As a carrier for the polishing slurry, it exhibits good solubility and compatibility, effectively dissolving various additives and dispersing nano-sized silica abrasives while avoiding corrosion of the KDP crystal surface. This enhances the stability of the polishing slurry, prevents stratification and precipitation during polishing, and simultaneously assists in achieving the formation of a high-precision, smooth surface in specific micro-regions.

[0042] The silica comprises 2-4% of the final polishing slurry by mass. As the abrasive in the polishing slurry, 20 nm-50 nm nano-sized silica is selected to match the soft and brittle characteristics of KDP crystals. Silica in this particle size range has high purity, uniform particle size, large specific surface area, moderate cutting force, and excellent dispersibility. It is used to achieve a gentle and efficient physical grinding action, accurately removing protrusions and micro-defects on the surface of KDP crystals, improving surface smoothness. Its hardness is precisely selected to balance grinding efficiency and crystal surface protection, avoiding excessive damage to the KDP crystal substrate and defects such as chipping and scratches. It can achieve high-precision polishing of specific micro-areas. At the same time, the nano-sized silica abrasive is easy to clean and leaves no residue, which can further ensure the cleanliness and optical performance of the crystal surface.

[0043] The deionized water, comprising 1-3% of the final polishing slurry, is used to assist in adjusting the viscosity and flowability of the polishing slurry, appropriately softening KDP to optimize the synergistic effect of physical grinding and chemical-assisted polishing. It also helps disperse nano-sized silica abrasives, preventing abrasive agglomeration (20 nm-50 nm nano-sized particles are prone to agglomeration; deionized water can effectively improve their dispersion stability), thus improving polishing uniformity. Furthermore, the deionized water undergoes rigorous purification to prevent the introduction of impurities that could contaminate the KDP crystal surface, ensuring high-precision polishing results in specific micro-regions.

[0044] The grape seed extract is a mature commercial product obtained by Shandong Jinsheng Technology Co., Ltd. It constitutes 0.5-1.5% of the final polishing solution by mass and is a natural additive used to improve the dispersibility, antioxidant properties, and environmental friendliness of the polishing solution. The proanthocyanidins it contains can adsorb onto the surface of nano-sized silica abrasives, forming steric hindrance and effectively preventing abrasive agglomeration, further optimizing the dispersion effect of the nano-sized abrasives, and reducing defects such as scratches and edge chipping during polishing. It also has good antioxidant properties, extending the shelf life of the polishing solution, replacing traditional toxic and harmful chemical additives, reducing environmental and health risks, and has no adverse reactions with KDP crystals, does not affect the crystal's optical properties, and ensures high-precision polishing results.

[0045] The second aspect of this invention provides a method for preparing the aforementioned polishing fluid, comprising mechanically stirring and mixing nano-sized abrasive silica, anhydrous ethanol, 2,3-butanediol, grape seed extract, and deionized water until uniform, followed by ultrasonic dispersion and magnetic dispersion. The specific steps are as follows:

[0046] (1) Anhydrous ethanol and 2,3-butanediol are mixed evenly by mechanical stirring at a speed of 1000-1200 rpm for 10-30 min to prepare mother liquor 0; wherein, the mass percentage of anhydrous ethanol in the mixed solution is 68.625%-72.75%, preferably 69.75%, and the mass percentage of 2,3-butanediol is 22.875%-24.25%, preferably 23.25%;

[0047] (2) Add nano-sized abrasive silica to mother liquor 0 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000-1200 rpm and the stirring time is 10-30 min to prepare polishing liquid 1. The mass ratio of nano-sized abrasive silica is 3-5% of the mass of the final polishing liquid, preferably 4%.

[0048] (3) Add deionized water to the above polishing liquid 1 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000-1200 rpm and the stirring time is 10-30 min to prepare polishing liquid 2. The mass ratio of deionized water is 1-3% of the mass of the final polishing liquid, preferably 2%.

[0049] (4) Add grape seed extract to the above polishing liquid 2 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000-1200 rpm and the stirring time is 10-30 min to prepare polishing liquid 3; wherein, the mass ratio of grape seed extract is 0-1.5% of the final polishing liquid mass, preferably 1%;

[0050] (5) The polishing liquid 3 is ultrasonically dispersed for 15-30 min at 25-30°C. Finally, a magnetic rotor is placed in the polishing liquid and the polishing liquid is placed on a magnetic stirrer with a speed of 600-800 rpm and a stirring time of 15-30 min, which forms the final polishing liquid 4.

[0051] The third aspect of the present invention also provides the application of the aforementioned polishing liquid or the polishing liquid prepared by the aforementioned method in the polishing process of KDP sample surface.

[0052] The fourth aspect of this invention, in conjunction with the accompanying drawings, specific polishing examples, and descriptions of their polishing applications, and presents comparative examples to demonstrate the excellent effects of the formulation:

[0053] Example 1

[0054] A method for preparing KDP crystal atomic-level surface polishing slurry and its application are disclosed. The components and their mass proportions in the final polishing slurry are as follows: nano-sized abrasive silica accounts for 3% of the final polishing slurry; deionized water accounts for 3% of the final polishing slurry; grape seed extract accounts for 1% of the final polishing slurry; and the mother liquor is a mixture of anhydrous ethanol and 2,3-butanediol. Specifically, the mixture contains 69.75% anhydrous ethanol and 23.25% 2,3-butanediol by mass.

[0055] The specific steps for preparing the above-mentioned KDP crystal atomic-level surface polishing slurry are as follows:

[0056] (1) 23.25 g of 2,3-butanediol and 69.75 g of anhydrous ethanol were mixed evenly by mechanical stirring at a speed of 1000 rpm for 15 min to prepare mother liquor 0.

[0057] (2) Add 3 grams of nano-sized abrasive silica to the mother liquor 0 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000 rpm and the stirring time is 15 min to make polishing liquid 1.

[0058] (3) Add 3 grams of deionized water to the above polishing solution 1 and mix evenly by mechanical stirring at a speed of 1000 rpm for 15 min to prepare polishing solution 2;

[0059] (4) Add 1 gram of grape seed extract to the above polishing liquid 2 and mix evenly by mechanical stirring at a speed of 1000 rpm for 15 minutes to prepare polishing liquid 3.

[0060] (5) The polishing liquid 3 was ultrasonically dispersed for 15 min at 25 ℃. Finally, a magnetic rotor was placed in the polishing liquid and the polishing liquid was placed on a magnetic stirrer with a speed of 800 rpm and a stirring time of 15 min to form the final polishing liquid 4.

[0061] Polishing process parameters: polishing pressure 30 kPa, polishing disc speed 70 rpm, polishing fluid flow rate 2 ml / min, polishing time 15 min.

[0062] The KDP crystal sample was a square block with a side length of 10 mm and a thickness of 5 mm. The surface Sa value of the polished KDP crystal was 0.301 nm, indicating high fineness of the polishing slurry. Within the measurement range of 50 × 50 μm², the PV value was 2.401 nm, demonstrating that the polished wafer exhibited no edge collapse or warping. The RMS value was 0.373 nm, indicating high optical quality of the polished KDP crystal surface, with high light transmittance, low scattering, and strong specular reflection. The material removal rate (MRR) was 941 nm / min. (See...) Figure 1 ).

[0063] Example 2

[0064] A method for preparing KDP crystal atomic-level surface polishing slurry and its application are disclosed. The components and their mass proportions in the final polishing slurry are as follows: nano-sized abrasive silica accounts for 3% of the final polishing slurry; deionized water accounts for 2% of the final polishing slurry; grape seed extract accounts for 1.5% of the final polishing slurry; and the mother liquor is a mixture of anhydrous ethanol and 2,3-butanediol. Specifically, the mixture contains 70.125% anhydrous ethanol and 23.375% 2,3-butanediol.

[0065] The specific steps for preparing the above-mentioned KDP crystal atomic-level surface polishing slurry are as follows:

[0066] (1) 23.125 g of 2,3-butanediol and 69.375 g of anhydrous ethanol were mixed evenly by mechanical stirring at a speed of 1000 rpm for 15 min to prepare mother liquor 0.

[0067] (2) Add 3 grams of nano-sized abrasive silica to the mother liquor 0 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000 rpm and the stirring time is 15 min to make polishing liquid 1.

[0068] (3) Add the 2 deionized water to the above polishing solution 1 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000 rpm and the stirring time is 15 min to prepare polishing solution 2;

[0069] (4) Add 1.5 g of grape seed extract to the above polishing liquid 2 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000 rpm and the stirring time is 15 min to prepare polishing liquid 3.

[0070] (5) The polishing liquid 3 was ultrasonically dispersed for 15 min at 25 ℃. Finally, a magnetic rotor was placed in the polishing liquid and the polishing liquid was placed on a magnetic stirrer with a speed of 800 rpm and a stirring time of 15 min to form the final polishing liquid 4.

[0071] Polishing process parameters: polishing pressure 20 kPa, polishing disc speed 80 rpm, polishing fluid flow rate 2 ml / min, polishing time 15 min.

[0072] The KDP crystal sample was a square block with a side length of 10 mm and a thickness of 5 mm. The surface Sa value of the polished KDP crystal was 0.293 nm (measured over a range of 50 × 50 μm²), the PV value was 2.716 nm, and the RMS value was 0.368 nm; the material removal rate (MRR) was 784.1 nm / min. (See...) Figure 2 ).

[0073] Example 3

[0074] A method for preparing KDP crystal atomic-level surface polishing slurry and its application are disclosed. The components and their mass proportions in the final polishing slurry are as follows: nano-sized abrasive silica accounts for 4% of the final polishing slurry; deionized water accounts for 2% of the final polishing slurry; grape seed extract accounts for 1% of the final polishing slurry; and the mother liquor is a mixture of anhydrous ethanol and 2,3-butanediol. Specifically, the mixture contains 69.75% anhydrous ethanol and 23.25% 2,3-butanediol by mass.

[0075] The specific steps for preparing the above-mentioned KDP crystal atomic-level surface polishing slurry are as follows:

[0076] (1) 23.25 g of 2,3-butanediol and 69.75 g of anhydrous ethanol were mixed evenly by mechanical stirring at a speed of 1000 rpm for 15 min to prepare mother liquor 0.

[0077] (2) Add 4 grams of nano-sized abrasive silica to the mother liquor 0 and mix evenly by mechanical stirring. The mechanical stirring speed is 1000 rpm and the stirring time is 15 min to make polishing liquid 1.

[0078] (3) Add 2 grams of deionized water to the above polishing solution 1 and mix evenly by mechanical stirring at a speed of 1000 rpm for 15 min to prepare polishing solution 2;

[0079] (4) Add 1 gram of grape seed extract to the above polishing liquid 2 and mix evenly by mechanical stirring at a speed of 1000 rpm for 15 minutes to prepare polishing liquid 3.

[0080] (5) The polishing liquid 3 was ultrasonically dispersed for 15 min at 25 ℃. Finally, a magnetic rotor was placed in the polishing liquid and the polishing liquid was placed on a magnetic stirrer with a speed of 800 rpm and a stirring time of 15 min to form the final polishing liquid 4.

[0081] Polishing process parameters: polishing pressure 10 kPa, polishing disc speed 60 rpm, polishing fluid flow rate 2 ml / min, polishing time 15 min.

[0082] The KDP crystal sample was a square block with a side length of 10 mm and a thickness of 5 mm. The surface roughness Sa of the polished KDP crystal was 0.284 nm (measured over a range of 50 × 50 μm²), the PV value was 2.456 nm, and the RMS value was 0.354 nm; the material removal rate (MRR) was 1019.4 nm / min. The surface roughness Sa of the polished KDP crystal under AFM was 0.301 nm (measured over a range of 5.2 × 5.1 μm²). (See...) Figure 3 ).

[0083] Comparative Example 1

[0084] The composition of the comparative polishing solution is similar to that in Example 3, except that grape seed extract is reduced. The proportions of the remaining components are the same as in Example 3. The preparation steps of the polishing solution are similar to those in Example 3, except that step 4 is omitted. The process used is the same as in Example 3. The surface roughness Sa value of the KDP crystal polished with this polishing solution is much greater than 0.287 nm, with a measurement range of 50 × 50 μm².

[0085] Comparative Example 2

[0086] The composition of the comparative polishing slurry is similar to that in Example 3, except that 2,3-butanediol is replaced with one of 1,3-butanediol, ethylene glycol, and 1,2-propylene glycol, while maintaining the same proportions. The remaining component proportions are the same as in Example 3, and the preparation steps and processes are the same as in Example 3. The surface roughness Sa values ​​of the KDP crystals polished with this slurry are all much greater than 0.287 nm, with a measurement range of 50 × 50 μm².

[0087] Comparative Example 3

[0088] The composition of the comparative polishing solution is similar to that in Example 3, except that deionized water is reduced. The proportions of the remaining components are the same as in Example 3. The preparation steps of the polishing solution are similar to those in Example 3, except that step 3 is omitted. The process used is the same as in Example 3. The surface roughness Sa value of the KDP crystal polished with this polishing solution is much greater than 0.287 nm, with a measurement range of 50 × 50 μm².

Claims

1. A KDP crystal atomic-level surface polishing slurry, characterized in that, The polishing solution is composed of the following components in the indicated mass percentages: 2-4% nano-sized silica, 1-3% deionized water, 0.5-1.5% grape seed extract, and the balance being a mixed alcohol; the mixed alcohol is a mixture of anhydrous ethanol and 2,3-butanediol. The anhydrous ethanol comprises 68.625% to 72.75% by mass, and the 2,3-butanediol comprises 22.875% to 24.25% by mass. A portion of the grape seed extract molecules dissolve in a mixed solvent composed of water and mixed alcohols, while another portion is adsorbed at the molecular level onto the surface of the nano-sized silica, forming a steric hindrance effect that hinders the aggregation of the nano-sized silica. The nano-sized silica is uniformly dispersed in the mixed solvent.

2. The KDP crystal atomic-level surface polishing slurry according to claim 1, characterized in that, The particle size of the nano-sized silica is 20~50 nm.

3. The KDP crystal atomic-level surface polishing slurry according to claim 1, characterized in that, The nano-sized silica, anhydrous ethanol, 2,3-butanediol, grape seed extract, and deionized water are first mixed evenly by mechanical stirring, and then evenly mixed by ultrasonic dispersion and magnetic dispersion.

4. The method for preparing the KDP crystal atomic-level surface polishing slurry according to claim 1, characterized in that, Includes the following steps: (1) Weigh the raw materials according to the mass ratio described above: nano-sized silica, deionized water, grape seed extract, anhydrous ethanol and 2,3-butanediol; Anhydrous ethanol and 2,3-butanediol were mixed evenly by mechanical stirring to prepare mother liquor 0; (2) Add nano-sized silica to mother liquor 0 and mix evenly by mechanical stirring to prepare polishing liquid 1; (3) Add deionized water to the above polishing liquid 1 and mix evenly by mechanical stirring to prepare polishing liquid 2; (4) Add grape seed extract to the above polishing liquid 2 and mix evenly by mechanical stirring to prepare polishing liquid 3; (5) The polishing liquid 3 is ultrasonically dispersed, and finally the polishing liquid is magnetically stirred by a magnetic rotor to obtain KDP crystal atomic-level surface polishing liquid.

5. The preparation method according to claim 4, characterized in that, In steps (1), (2), (3) and (4), the mechanical stirring speed is 1000-1200 rpm and the stirring time is 10-30 min.

6. The preparation method according to claim 4, characterized in that, In step (5), the ultrasonic dispersion process involves an ultrasonic time of 15–30 min and an ultrasonic temperature of 25–30 °C.

7. The preparation method according to claim 5, characterized in that, In step (5), the magnetic stirring speed is 600~800 rpm and the stirring time is 15~30 min.

8. The application of the KDP crystal atomic-level surface polishing slurry according to claim 1, characterized in that, Polish the KDP crystals using the following parameters: polishing pressure 20~30 kPa, polishing disc speed 70~80 rpm, polishing fluid flow rate 2 ml / min, polishing for 15 min.

9. The application according to claim 8, characterized in that, The KDP crystal is a square with a side length of 10 mm and a thickness of 5 mm.

10. The application according to claim 8, characterized in that, Under the condition that the measurement range does not exceed 50×50 μm², after polishing, the KDP crystal has a surface arithmetic mean height Sa value of less than 0.301 nm, a peak-to-valley value PV value of less than 2.716 nm, and a root mean square roughness rms value of less than 0.373 nm.

11. The application according to claim 8, characterized in that, The material removal rate (MRR) was 784.1–941 nm / min.

Citation Information

Patent Citations

  • Polishing solution for KDP (potassium dihydrogen phosphate) crystal and efficient grinding and polishing process

    CN115181498A

  • Scintillation crystal polishing solution and preparation method thereof

    CN120310439A